EFISIENSI TEKNIS USAHATANI KOPI DI KABUPATEN TANA TIDUNG (KTT) - Elly Jumiati dan Sekar Inten Mulyani (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2014)
Technical Efficiency of Coffee Farming in Tana Tidung Regency (KTT). This study aims to know the technical efficiency of a coffee farmin in KTT. This research was conducted in Tana Tidung precisely in the Buang Baru village as the coffee development center. Samples were taken of 30 people who have been producing coffee farmers. the data Analysis used to measure the technical efficiency  was stochastic frontier function with Frontier program 4.1.c.The results showed that the technical efficiency of a coffee farm in KTT was not efficient yet. The value of technical efficiency (ET) average farmer of 0.75 or 75%. Based on the results of the estimation of Stochastic Frontier production function with the MLE method on coffee farming which significantly affect the technical efficiency is negative and coffee farming is the outpouring of labor, the amount of the amount of herbicide and amount of manure. While the efficiency factors that influence real and positive is the amount of KCl. The factors that influence the production inefficiency is the number of family members.